Traversing Magical Realism in Postcolonial Literature - Sri Nurhidayah; Rahmat Setiawan (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
This article aims at traversing historical traces, concepts, and characteristics of magical realism and how it is pertinent in literary analysis. The pivot of the conceptual framework of this article in on Faris’ perspective on magical realism. The approach of this study is grounded theory. The data are quotations taken from referential books and journals. The techniques of data collection are documentation and quoting. The technique of analysis is thematic interpretation. This article figures out that magical realism deconstructs the status of magical and the real into a somersaulting realm. Western historical narrative establishes the real through rationality and alienates the magical which is identical to the East, the Other, or the indigenous. This rational narrative is propagandized and turns to be power relation. Therefore, magical realism, through some literary works, deconstructs the rational perspective with logical-magical narrative as one of postcolonial studies.